TIME ANALYSIS OF THE MIXING PROCESS OF FIRE BRICK MATERIALS IN PT. BENTENG API TECHNIC GRESIK - Wirawan, Andika Puji; Arief, Zainal (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
PT. Benteng Api Technic is a leading refractory company in Indonesia with refractory bricks as one of its superior products. The process of making refractory bricks that will be observed in this study is the process of mixing materials and the molding process. In the mixing process, there are no tools in the form of time indicators to help operators make decisions about the mixing time of ingredients. This research aims to obtain the time for the mixing of materials with maximum mixing quality and to support the press process optimally. The research was conducted using a perfectly randomized experimental design in order to obtain different mixing results based on the nine selected mixing time treatments. Measurement of working time is carried out using the stopwatch time study method on press operators who are experienced in their fields. Calculations to align the two processes using a Gantt chart with idle time as an indicator. The experimental results revealed that the most optimal mixing with a mixing time of 12 minutes resulted in 7.2 kilograms of mass that did not pass through an 18 mesh sieve. Based on the results of the gantt chart, the use of 11 mixing time for material B resulted in the lowest idle time of 178 minutes. The processing time obtained is expected to be used as a guide in determining the time input on the time indicator tool in the process of mixing refractory bricks.